OXIDATIVE STRESS AND PHYSICAL ACTIVITY - Dragan Radovanović; Marija Stanković (University of Banja Luka, Faculty of physical education and sport, 2012)
The cells continuously produce free radicals and reactive oxygen species as a part of metabolic processes. Increased aerobic metabolism during exercise is a potential source of oxidative stress. Also, anaerobic physical activity and oxidative stress are interrelated because the intense anaerobic activity leads to damage proteins, lipids and nucleic acids in muscle cells and blood. Complex system of antioxidant defense, which has the enzymatic and non-enzymatic part, has a role in protecting tissues from excessive oxidative damage. Most of the research conducted so far about the impact of various forms of physical activity on levels of oxidative stress is confirmed by changes in biomarkers that indicate lipid peroxidation and proteins modification. Untrained persons, as opposed to trained, are more susceptible to major changes in the body caused by oxidative stress during physical activity. The results of researches have shown that there are no significant differences between the genders in the level of oxidative stress during physical activity and response to antioxidant supplementation possibly applied. It is interesting that, despite of numerous studies, the exact location of oxidative stress origin during physical activity has not been reliably established. In addition, research results provide insufficient evidence on the effectiveness of using antioxidant supplementation to increase the defense against oxidative stress. It is necessary further investigation about the redox status and oxidative stress during physical activity in adolescent athletes.